2020
DOI: 10.1002/smtd.202000889
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Inkjet Printing Patterned Lead Halide Perovskite Quantum Dot Color Conversion Films by Using Cheap and Eco‐Friendly Aqueous Inks

Abstract: Inkjet‐printed perovskite quantum dot (PQD) color conversion films (CCFs) have great potentials for mini/micro‐LED displays because of their ultrahigh color purity, tunable emissions, high efficiency, and high‐resolution. However, current PQD inks mainly use expensive, toxic, and flammable organic substances as solvents. In this work, water is proposed to be used as the solvent for inkjet printing PQD/polymer CCFs. The green‐emitting patterned MAPbBr3/polyvinyl alcohol (PVA) films are in situ prepared by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 68 publications
0
59
1
Order By: Relevance
“…To date, inkjet printing techniques have been used to deposit QDs directly onto the chip surface 15 or onto a transparent substrate, forming a pattern that covers the chip array. According to the different strategies of driving the ink, there are aerosol inkjet printing (AJP) 16 , piezoelectric inkjet printing (IJP) 17,18 , and electrohydrodynamic (EHD) inkjet printing 19 . All these strategies, by exerting some external forces, eject the ink through the nozzle.…”
Section: Micro-led and Inkjet Printingmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, inkjet printing techniques have been used to deposit QDs directly onto the chip surface 15 or onto a transparent substrate, forming a pattern that covers the chip array. According to the different strategies of driving the ink, there are aerosol inkjet printing (AJP) 16 , piezoelectric inkjet printing (IJP) 17,18 , and electrohydrodynamic (EHD) inkjet printing 19 . All these strategies, by exerting some external forces, eject the ink through the nozzle.…”
Section: Micro-led and Inkjet Printingmentioning
confidence: 99%
“…The surface tension of the mixed solvent with 20 vol % 1,2-dichlorobenzene and 80 vol % cyclohexylbenzene reduced to 31.77 43 , John Wiley and Sons; (c) ref. 17 , American Chemical Society; (d-f) ref. 91 , AIP Publishing.…”
Section: For Piezoelectric Inkjet Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…Perovskite quantum dots (PQDs) have become a significant area in display technology research owing to their distinct optical properties, including a tunable wavelength and narrow wavelength [199]. Shi et al [200] inkjet-printed PQD inks with water as a solvent. Yoo et al [201] printed with a perovskite ink on an ethyl cellulose film and concluded that a (3-aminopropyl) trimethoxysilane (APTES)-coated red perovskite ink had improved drying stability.…”
Section: Display Technology Has a Ubiquitous Effect In Daily Lifementioning
confidence: 99%
“…As a rule of thumb, a range of 1 < Z < 14 is considered suitable for IJP. [45] Cyclohexylbenzene is selected as a suitable solvent for the ink, which can maintain the excellent luminescence performance of the PeQDs and exhibit a good IJP (Figure S6, Supporting Information) ability with a Z value of 9.02 (e.g., the nozzle diameter is 20 μm, the density is 0.96 g mL −1 , the surface tension is 35.69 N m −1 , and the viscosity is 2.9 cP). The structure of PeLEDs typically consists of a multilayer of indium tin oxide (ITO)/poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS)/poly(9-vinylcarbazole) (PVK)/PeQD/1,3,5-tris(1phenyl-1H-benzimidazol-2-yl)benzene (TPBi)/LiF/Al.…”
Section: Fabrication and Structure Of Micro-peled Arraysmentioning
confidence: 99%